ICT Augmented Elementary Teaching and Learning - KANVARIA, VINOD (THE PRIMARY TEACHER, 2015)
Technology, to a layman, means some strategy, apparatus, instrument or practice, which can make a work easier, efficient, requiring lesser efforts, lesser time, lesser labour, and lesser money. In other words, technology is the one, which saves time and energy while pursuing a particular task. Being so useful, technology has encrypted in almost every sphere of human life, including the education. In the sphere of education, transforming from effective strategies for teaching learning, as earlier concept of ‘technology of education’, technology has, now, taken a different shape as of using effective apparatus, instruments, platforms and resources for effective teaching-learning, which can be said as ‘technology in education’. Technology, now, means not only the content creation, but also to communicate it effectively to the prospective learners and opening up a new door for enhancing creativity among them, believing in the principles of constructivism.